Overview of Public Safety Center (PSC) 119 Call Patterns in Semarang City in 2024 as a Basis for Strengthening the Emergency Response System - Salma Aulia Ramadhani; Anisya Ayu Febriyanti; Muhammad Farhan Agung Nugroho; Melinda Valerie Tunggal Djaja; Jevita Sri Nurhayati Loleh; Respati Wulandari; Ahmad Zaini; Wisnu Wardana; Ira Anggraini; Rustiyana Wuri Handayani (VISIKES, 2026)
The Public Safety Center (PSC) 119 service is an integrated emergency medical system that plays a crucial role in Indonesia's pre-hospital healthcare system. The demand pattern for PSC-119 services can be influenced by various factors, including weather conditions and community mobility. In Semarang City, no research has described the weekly trends of PSC-119 calls based on case types and their relationship with weather parameters. This study aims to describe the weekly trend patterns of PSC-119 calls based on case types and compare them with weather pattern changes in Semarang City in 2024. This study employed a quantitative-descriptive method with a time-based descriptive analysis approach. Secondary data included PSC-119 calls categorized by case type (transportation, homecare, general emergency, traffic accidents, and non-emergency) and weekly weather data (temperature, humidity, rainfall) from the Central Java Climatology Station for January-December 2024. Descriptive analysis was performed with visualization using weekly trend charts. Total PSC-119 calls in 2024 showed weekly variations with the highest peak in week 8 at 633 calls. Transportation category dominated with 11,825 calls, followed by homecare (4,339 calls). Peak calls occurred during relatively dry weather conditions (rainfall 3.1 mm, temperature 29.6°C, humidity 77.7%). Comparative analysis showed that weather variable changes did not form patterns consistent with weekly call fluctuations. Fluctuations in PSC-119 calls in Semarang City were more influenced by activity patterns and community mobility than by weather variables. Weather acts as an enabling factor that supports increased mobility, rather than as a direct determinant of emergency incidents.